Risk factors for rebleeding in patients with obscure gastrointestinal bleeding from southern China. Issue 10 (October 2021) - Liu, Boying; Liu, Sudong; Wen, Pingwu; Wang, Shengbing; Wang, Fuqun; Gu, Xiaodong
Background: To identify the risk factors associated with rebleeding in obscure gastrointestinal bleeding (OGIB) patients from southern China. Methods: This retrospective study involved 229 patients who underwent small bowel endoscopy in our hospital between 1 January 2018 and 1 December 2020. The clinical characteristics and risk factors related to rebleeding were retrospectively evaluated. Results: Rebleeding patients were significantly older than non-rebleeding patients (53.0 ± 15.9 vs. 46.2 ± 17.8 years), had lower hemoglobin concentrations (89.2 ± 28.1 vs. 126.2 ± 25.1 g/L), and higher blood urea nitrogen concentrations (5.4 ± 2.6 vs. 4.5 ± 2.2 µmol/L), respectively. A higher percentage of rebleeding patients had diabetes mellitus (13.9% vs. 2.9%) and overt bleeding (70.4% vs. 38.6%), and required blood transfusions (43.1% vs. 8.0%), compared with non-rebleeding patients, respectively. Multivariate logistic analysis indicated that drinking alcohol (odds ratio (OR): 9.27; 95% confidence interval (CI) = 1.35–63.78), anemia (OR: 17.38; 95% CI = 5.48–55.10), and blood transfusion (OR: 3.76; 95% CI = 1.04–13.56) increased the risk of rebleeding in OGIB patients. Conclusion: Our data suggested that OGIB patients who drink alcohol, have anemia, and require blood transfusion have an increased risk of rebleeding.